PENYELESAIAN PERKARA TINDAK PIDANA PENGHINAAN DAN ATAU PENCEMARAN NAMA BAIK SEBAGAIMANA DIATUR DALAM UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (ITE) DENGAN PENDEKATAN KONSEP RESTORATIVE JUSTICE - Rudi Santosa (Legal Spirit, 2022)
This research results, First, criminal acts of humiliation and or defamation are generally regulated in the Criminal Code, but are also specifically regulated in the Law on Electronic Information and Transactions (ITE). The application of criminal provisions in case of violating the prohibition in Article 27 Paragraph (3) is applied according to the type of criminal act that has been legally proven to be carried out by the perpetrator of the crime. Second, for this defamation case, other steps can be taken that can achieve the purpose of sentencing, such as settlement through a restorative justice approach, this is also in line with the recommendation of the National Police Chief through Circulars and Prosecutors' Regulations regarding the settlement of criminal cases through a restorative justice approach.